Peran Guru dalam Peningkatan Mutu Pendidikan: Penting dan Genting! - Reggy Maulansyah; Dila Febrianty; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2023)
The aim of this study is to find out that teachers are a component in improving the quality of education. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from Prof. Prof.'s YouTube channel. Dr. Dasiem Budimansyah entitled "Teachers are the Most Important Component in Improving the Quality of Education" which he explained. The results of this study explain that the most important component in improving the quality of education is the quality of the teacher profession. Quality education will never be realized without teachers who are competent and managed efficiently so that their performance is professional. With the help of school leaders aimed at developing the leadership of teachers and other school personnel in achieving educational goals in the form of encouragement, guidance and opportunities for the growth of teachers' skills and abilities such as guidance and reform efforts in education and teaching. As well as learning organizational culture and training activities. To achieve its goals, this approach must be carried out in a directive, collaborative or non-directive manner, taking into account the level of conceptual maturity and commitment of a teacher.